INSTALLATION OF PUBLIC FACILITIES LIGHTING IN PASA LIMAU PARIT MALINTANG - Muknizar, Muknizar; mallisza, Danyl Mallisza; Slamet Riyadi; Risal Abu; Dewirman Prima Putra; Ahmad Fikri; Niko Zainuddin Muchtar; Muhammad Alimuddin Hafidz; Raden Roro Anggun Tutur Winasis; Raka Putra Hanafi; Asrul, Asrul; Putra Hajril Fajri; Refnaldi Pramana (Ikatan Dosen Menulis, 2026)
Korong Pasa Limau is one of the villages in Nagari Parit Malintang, where the village has a surau (prayer hall) that has just been built and is located among the Guci community. The problem faced by the residents of Korong Pasa Limau is the safety of residents who want to pray at the newly built surau, named Surau Sungsang. Before Surau Sungsang was built by the residents of Korong Pasa Limau, the korong already had a surau located downhill, so residents who wanted to pray had to walk down and were at risk of falling or slipping on the descending path leading to that surau. Student Real Work Lecture (KKN-PPM) community service activities are carried out to solve problems that occur in the environment. One of them is by providing public facilities in the form of lighting at Surau Sungsang for residents to be able to start worshiping there. Students from Group 22 of KKN-PPM UNES 2024 installed lighting for Surau Sungsang using an electric power source from PLN, with a total of 8 light installation points at Surau Sungsang, Korong Pasa Limau.